Transformation of the agricultural financial system in the age of globalisation - Brzozowska, Anna; Bubel, Dagmara; Kalinichenko, Antonina; Nekrasenko, Larysa (My University, 2017)
The paper is an attempt to address the advantages and risks connected with the wave of financial globalisation, with a focus on its impact on financial policy in European agriculture. The aim of the paper is to identify the basic conditions of the functioning and change of the financial system of agriculture under the conditions of the globalisation of financial markets. Financial globalisation, also referred to as financial integration or openness, is understood as an increase in global ties and interdependences caused by capital flows. Potentially, globalisation can bring a lot of benefits, which are manifested in an acceleration of economic growth and decreased fluctuation in consumption, which should further improve the level of overall prosperity. On the other hand, however, internationalisation of financial flows entails a range of threats, including the possibility of crisis.
Keywords: agribusiness; budget deficit; economic crisis; food markets; internationalisation; monetary policy; public debt